Cancellation of nonlinear inter-carrier interference in OFDM systems with nonlinear power-amplifiers - Fernandes, Carlos Alexandre Rolim (2010)
Due to a high peak-to-average power ratio (PAPR), orthogonal frequency division multiplexing (OFDM) signals are often driven at the nonlinear region of power amplifiers (PAs). As a consequence, the orthogonality between the subcarriers is broken and nonlinear intercarrier interference (ICI) is introduced. In this paper, we proposed two techniques for canceling nonlinear ICI in wireless OFDM communication systems with nonlinear PAs. The proposed techniques are based on the concept of power diversity, which consists in a transmission scheme that re-transmits the symbols several times with a different transmission power each time. The main advantage of using the power diversity is that the problem of canceling the nonlinear ICI can be viewed as a source separation problem, where the ICI terms correspond to “virtual” sources. The proposed techniques are able to provide a more robust transmission at the cost of a lower transmission rate.